KEMAMPUAN PENALARAN MATEMATIS DALAM MENYELESAIKAN SOAL CERITA BAGI SUBJEK PROGRAM PEMINATAN BAHASA DAN IPS - Dita Kusuma Anggraeni; Abdul Halim Fathani; Alifiani Alifiani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This study aims to describe the ability of mathematical reasoning in solving story problems for students of the Language and Social Studies specialization program. The approach in this study is descriptive qualitative. The subjects of this study are students who have high mathematical abilities in the Language and Social Studies specialization program in Class XI SMA Negeri 7 Malang. The data collection techniques used are tests, interviews, and documentation. Data analysis is carried out through 3 stages, namely data condensation, data presentation, and drawing conclusions. Based on the results of data analysis, the following findings were obtained. In the sensemaking process, learners are equally inclined to represent visual and symbolic forms. In the conjectturing process, language subjects have linguistic intelligence, while social studies subjects have intrapersonal intelligence. In  the convincing process, the subject of Language corresponds to a predetermined settlement strategy but there are errors in the calculation process and tend to use the right brain. While the subject of IPS corresponds to a predetermined settlement strategy and is not written down the process of calculating it but the results are correct and tend to use the right brain. In  the reflecting process, the Language subject reevaluates the completion result but is less sure, while the IPS subject reevaluates the completion result and is confident so that the completion result is correct. In the process  of generalising,  the subject of Language generalizes conclusions using words but incorrectly. Meanwhile, the subject of IPS generalizes conclusions correctly and uses words in writing down the conclusions of the answers. Based on the results of the study, language subjects are known to have poor mathematical reasoning skills, which can perform all indicators but there are errors in the stages of the indicators. Meanwhile, IPS subjects have good mathematical reasoning abilities by fulfilling all stages and indicators of mathematical reasoning ability